STRATEGI COOPERATIVE DALAM MENGATASI KESULITAN MEMBACA AL-QUR’AN PADA SISWA - Ulfia Fiqri Aulia; Nurul Latifatul Inayati (PAI RAFAH, 2023)
This study aims to explore the effectiveness of cooperative strategies in overcoming Quran reading difficulties for students. The problem-solving method was used as the main approach in this study, with the aim of improving Quran reading skills. The research was conducted through group learning involving all students of SMA Muhammadiyah 1 Surakarta. This research is a field research that uses a phenomenological approach with qualitative methods. The research location is on Jl. R.M. Said No.35 Ketelan, Banjarsai District, Surakarta City, Central Java. The data collection techniques used were participant observation, interviews and documentation, where students and teachers of Baca Tulis Alqur'an became the research subjects. The results showed that the application of cooperative strategies was able to overcome the difficulty of reading the Quran for students. In the context of group learning, students can collaborate with each other in solving problems that arise when reading the Quran. This process helps improve students' understanding of Quranic reading and also motivates them to be more active in participating in learning. The findings of this study have important implications for Quran education in schools. Cooperative strategies can be used as an effective alternative in overcoming students' difficulties in reading the Quran. This study also highlights the importance of cooperation and collaboration in learning the Qur'an as well as its contribution to the learning process.